Antibiotics, nutrients and thermotherapy as control methods for Huanglongbing (HLB) - Martínez-Padrón, Hadassa Yuef; Sáenz-Pérez, Criseida Alhelí; Paredes-Sánchez, Francisco Alejandro; Herrera-Mayorga, Verónica; Rodríguez-Herrera , Raúl; Osorio-Hernández, Eduardo (Revista Mexicana de Ciencias Agrícolas, 2025)
Huanglongbing (HLB), also known as greening disease or citrus greening, is a bacterial disease that affects citrus worldwide. This disease causes yellowing of the leaves, deformities in the fruits and eventually, the death of the tree. Currently, there is no cure for Huanglongbing; therefore, control focuses on preventing and mitigating the disease. The present research aimed to discuss the different control methods that are currently applied to control Huanglongbing, among which antibiotics, nutrients, and thermotherapy stand out. Antibiotics have been shown to be effective in controlling Huanglongbing in controlled studies. Nevertheless, their widespread use is limited due to concerns about antibiotic resistance. On the other hand, the application of certain nutrients, such as zinc and phosphorus, has shown promising results in improving the tolerance of citrus to Huanglongbing. These nutrients strengthen the plant’s immune system and make it more resistant to infection. Finally, thermotherapy has proven to be an effective method to eliminate the Huanglongbing bacteria. Controlling Huanglongbing in citrus requires an integrated approach that combines different methods, such as the use of specific antibiotics, nutrient application, and thermotherapy. Continued research is needed to develop more effective, sustainable, and economically viable control methods to protect this important agricultural industry.